Concordância do International Physical Activity Questionnaire com o pedômetro, em mulheres pós-menopausadas portadoras de osteoporose - Dallanezi, Glauber; Corrente, José Eduardo [UNESP]; Freire, Beatriz Funayama Alvarenga [UNESP]; Mazeto, Gláucia Maria Ferreira Silva [UNESP] (My University, 2011)
Background and objectives: Osteoporosis is a serious public health problem. Physical activity (PA) represents an important step towards the preservation / restoration of bone health. The International Physical Activity Questionnaire (IPAQ), which represents a useful tool in the evaluation of PA in various situations, has not yet been validated for patients at higher risk for disease, or postmenopausal women. The aim of this study was to evaluate the concordance between IPAQ and the pedometer, in osteoporosis carrier postmenopausal women. Method: This is the study of a case series, in a transversal and descriptive way. We have evaluated 21 osteoporosis carrier postmenopausal women, followed in a specialized ambulatory. The used tools were the IPAQ long form and the pedometer. The concordance factor (CF, %) and the kappa index (k) were evaluated between the two methods. Results: The patients presented an average age of 63.43 ± 10.42 years and an average body mass index of 25.74 ± 4.75 kg/ m2 . According to the IPAQ, 42.8% of patients were considered as very physically actives; 28.6%, as physically active and 28.6%, as sedentary. The CF between IPAQ and the pedometer, considering the number of steps, was of 47.6%, with a k of 0.21; when the caloric waste was taken into account, the CF between the two instruments was of 42.9%, with a k=0.13. Conclusion: We can therefore conclude that IPAQ, when applied to osteoporosis carrier postmenopausal women, presents slight to moderate concordance with the obtained pedometer data.

Justificativa e Objetivos: A osteoporose se constitui em um grave problema de saúde pública. A atividade física (AF) representa importante medida para a manutenção/recuperação da saúde óssea. O International Physical Activity Questionnaire (IPAQ), o qual representa uma ferramenta útil na avaliação da AF em diversas situações, ainda não foi validado para as pacientes de maior risco para a doença, ou seja, mulheres pós-menopausadas. O objetivo deste estudo foi avaliar a concordância entre o IPAQ e o pedômetro, em mulheres pós-menopausadas, portadoras de osteoporose. Método: Trata-se de estudo de série de casos, transversal e descritivo. Foram avaliadas 21 mulheres pós-menopausadas, portadoras de osteoporose, acompanhadas em ambulatório especializado. Os instrumentos utilizados foram o IPAQ, forma longa e o pedômetro. Foram avaliados o coeficiente de concordância (CC, %) e o índice kappa (k) entre os dois métodos. Resultados: As pacientes apresentaram idade média de 63,43 ± 10,42 anos e índice de massa corpórea médio de 25,74 ± 4,75 kg/m2 . De acordo com o IPAQ, 42,8% das pacientes foram consideradas como muito ativas, 28,6% como ativas; e 28,6%, como sedentárias. O CC entre o IPAQ e o pedômetro, considerando-se o número de passos, foi de 47,6%, com k de 0,21, e levando-se em conta o gasto calórico, de 42,9%, com k = 0,13. Co nclusão: O IPAQ quando aplicado em mulheres pós- -menopausadas e com osteoporose, apresenta concordância leve a moderada com os dados obtidos com o pedômetro.
Concordance of the International Physical Activity Questionnaire with the pedometer, in postmenopausal women with osteoporosis
Keywords: Exercise; Motor activity; Osteoporosis; Atividade física; Exercício; Osteoporose